2007
DOI: 10.1152/ajplung.00050.2007
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cell replacement with bone marrow cells for airway epithelial regeneration

Abstract: It has been suggested that some adult bone marrow cells (BMC) can localize to the lung and develop tissue-specific characteristics including those of pulmonary epithelial cells. Here, we show that the combination of mild airway injury (naphthalene-induced) as a conditioning regimen to direct the site of BMC localization and transtracheal delivery of short-term cultured BMC enhances airway localization and adoption of an epithelial-like phenotype. Confocal analysis of airway and alveolar-localized BMC (fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 46 publications
3
88
0
5
Order By: Relevance
“…Bone marrow-derived cells have been suggested to give rise to lung epithelial cells in vitro (7,35) and in vivo (2,5,13). However, the precise fate of specific BMCs has not been well characterized to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bone marrow-derived cells have been suggested to give rise to lung epithelial cells in vitro (7,35) and in vivo (2,5,13). However, the precise fate of specific BMCs has not been well characterized to date.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse whole bone marrow was harvested and cultured as previously described (13). Cells were cultured in DMEM (Invitrogen) supplemented with 10% FBS (Invitrogen) and 1% penicillin-streptomycin (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] However, with refi ned research techniques, MSC engraftment seems to be a rare event 22,23 of unclear physiological signifi cance. 13,24 A growing number of studies have shown that MSCs have immunomodulatory and anti-infl ammatory eff ects despite minimum or absent engraftment.…”
Section: Reviewmentioning
confidence: 99%